Cameras: Forms of Interaction - Mangano, Dario (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2008)
This essay examines the material design of cameras. The author argues that design plays a central role in the interaction between Operator and Spectator (R. Barthes) and, furthermore, that it entails significant effects on photographic aesthetics. Finally, the author also considers some of the design differences between traditional emulsion cameras and digital cameras.